Multi-locus genome-wide association study of fusarium head blight in relation to days to anthesis and plant height in a spring wheat association panel - Cabral, Adrian L.; Ruan, Yuefeng; Cuthbert, Richard D.; Li, Lin; Zhang, Wentao; Boyle, Kerry; Berraies, Samia; Henriquez, Maria Antonia; Burt, Andrew; Kumar, Santosh; Fobert, Pierre; Piche, Isabelle; et al. (Frontiers in Plant Science, 2023)
Fusarium head blight (FHB) is a highly destructive fungal disease of wheat, to which host-resistance is quantitatively inherited, and largely influenced by the environment. Resistance to FHB has been associated with taller height and later maturity, however a further understanding of these relationships is needed. An association mapping panel (AMP) of 192 predominantly Canadian spring wheats genotyped with the wheat 90K SNP array was assessed for FHB incidence (INC), severity (SEV) and index (IND), days to anthesis (DTA) and plant height (PLHT) between 2015 and 2017 at three Canadian FHB inoculated nurseries. Seven multi-environment (MET) datasets were deployed in a GWAS using a single-locus Mixed Linear Model (MLM) and a multi-locus random SNP-effect Mixed Linear Model (mrMLM). MLM detected four quantitative trait nucleotides (QTN) for INC on chromosome 2D and 3D, and for SEV and IND on 3B. Further, mrMLM identified 291 QTN: 50 (INC), 72 (SEV), 90 (IND), 41 (DTA) and 38 (PLHT). At two or more environments, 17 QTN for FHB, DTA and PLHT were detected: 12 pleiotropic for FHB traits, DTA and PLHT on chromosome 1A, 1D, 2D, 3B, 5A, 6B, 7A and 7B; two QTN for DTA on 1B and 7A; and three for PLHT on 4B and 6B. Of these 17, the 1B DTA QTN, and the three pleiotropic QTN on 1A, 3B and 6B are potentially identical to corresponding quantitative trait loci (QTL) in durum wheat. Further, the 3B pleiotropic QTN for FHB INC, SEV and IND co-locates with TraesCS3B02G024900 within the Fhb1 region on chromosome 3B, and is ~3 Mb from a cloned Fhb1 candidate gene TaHRC. While the PLHT QTN on 6B is putatively novel, the 1B DTA QTN co-locates with a disease resistance protein located ~10 Mb from a Flowering Locus T1-like gene TaFT3-B1, and the 7A DTA QTN is ~5 Mb away from a maturity QTL QMat.dms-7A.3 of another study. Deploying the IWGSC RefSeq versions 1.0 and 2.1 in our QTN-candidate gene approach to characterizing FHB resistance in relation to DTA and PLHT should eventually generate additional and reliable trait-specific markers for breeding-selection, besides provide useful information for FHB trait-discovery.